Networks, Communication and Hierarchy: Applications to Cooperative Games - Encarnacion Algaba; Rene van den Brink (Tinbergen Institute, 2021)
Agents participating in different kind of organizations, usually take different positions in some network structure. Two well-known network structures are hierarchies and communication networks. We give an overview of the most common models of communication and hierarchy restrictions in cooperative games, compare different network structures with each other and discuss network structures that combine communication as well as hierarchical features. Throughout the survey, we illustrate these network structures by applying them to cooperative games with restricted cooperation.
Keywords: C71; 330; Networks; games; communication; hierarchy; cooperative TU-game; Shapley value